Role of cpxA Mutations in the Resistance to Aminoglycosides and β-Lactams in Salmonella enterica serovar Typhimurium - Jing, Wenxian; Liu, Juan; Wu, Shanshan; Li, Xuerui; Liu, Yongsheng (Frontiers in Microbiology, 2021)
Although it has been reported that the deletion of response regulator CpxR in CpxRA system confer sensibility to aminoglycosides (AGAs) and β-Lactam in S. enterica serovar Typhimurium, the regulating effect of CpxA on multi-drug resistance (MDR) has not been fully discussed in S. enterica serovar Typhimurium. Here, to explore the role of CpxA on MDR, various cpxA mutants with null mutant (JSΔcpxA), site-direct mutant (JSΔCpxA38), internal in-frame deletion mutant (JSΔcpxA92-104) of S. enterica serovar Typhimurium JS strain were constructed. It was revealed that cpxA and cpxR deletion mutants have opposing roles in the regulation of resistance to AGAs and β-lactams. Amikacin and cefuroxime can activate CpxRA system, which result in increased resistance of WT compared with the CpxR deletion mutant. All the cpxA mutations significantly increased resistance to AGAs and β-lactams due to the CpxRA system activation via phosphorylation of CpxR. Moreover, AckA-Pta-dependent activation of CpxR increases antibiotic resistance of cpxA deletion mutation. Further researches on the relationship between CpxRA system and AcrAB-TolC efflux pump revealed that the deletions of acrB and tolC decrease AGAs and β-lactams resistance, but don’t influence the resistance regulation of CpxRA on these antibiotics. The detection of candidate MDR-related CpxR regulons revealed that the mRNA expression levels of spy, ycca, ppia, htpX, stm3031 and acrD were up-regulated and ompW were down-regulated in various cpxA mutants. These results suggested that cpxA mutations contribute to AGAs and β-lactams resistance depended on CpxR by influencing a comprehensive factors, which is related to genes related to protease, protein folding, outer membrane proteins and efflux pumps in S. enterica serovar Typhimurium.